Effects of short-term training on pastoral community employment creation and livelihood improvement: A study on selected Ethiopian pastoral areas - Robson Mekonnin Shiferaw (Journal of Innovation and Entrepreneurship, 2020)
This study investigated the effects of a short-term training on pastoral community employment creation and livelihood improvement. The study investigated the perception of beneficiaries pertinent to the benefits of a short-term training scholarship, experiences of graduate trainees, estimation of employability rate after training, and types of employment TVET graduates are engaged during the year 2014 to 2017 in Pastoral Resilience Improvement through Market Extension project operating clusters. Self-administered survey questionnaires were used and distributed to 128 project beneficiaries in Afar, Eastern, and Southern clusters of Ethiopia. Since the instrument was close-ended questionnaires in the form of a dichotomous, and quantitative research approach was deployed. The quantitative part of the assessment was analyzed using descriptive and inferential statistics with the support of SPSS version 20. The finding of the study indicated that the reasons for unemployment of the beneficiaries were mainly lack of financial support and poor industry linkage with employers in the areas. On the other hand, such activities should be assessed once again for financial and material support since the majority of the trainees were unemployed and seeking support besides the training received from the program in all clusters from all concerned development partners. The finding of the study depicted, gender-related issues in all clusters implies that women involvements or participation shows a variation in some clusters. However, the project more benefited male beneficiaries than women in all clusters. Therefore, if the project will continue this type of program, balancing gender and equal benefit should be maintained in all clusters. Redesigning the program is required because due to providing training alone cannot bring livelihood changes as the finding of the study revealed. This is because the beneficiaries of the program were selected from an economically poor family background. Therefore, the program should evaluate once again for financial and equipment support since the majority of the trainees were unemployed and seeking support from different development stakeholders in the three clusters.
Keywords: 650; Short-term training; Livelihood change; Job creation; Pastoral; Community